2000
DOI: 10.1039/b001937m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultra-high purity trialkylgallium MOVPE precursors. Crystal structures of triethylgallium and triisopropylgallium adducts with macrocyclic tertiary amines

Abstract: A synthesis and puri®cation route has been developed for base-free trialkylgallium compounds which avoids the use of traditional ether solvents. The R 3 Ga compound (R~Et, Pr i ) is synthesised in triethylamine, NEt 3 , which leads to the adducts R 3 Ga(NEt 3 ). The NEt 3 ligand can be readily displaced by the addition of low volatility bidentate, tetradentate or hexadentate tertiary amines to give adducts of the type (R 3 Ga) x L (x~2, 4, 6), from which base-free R 3 Ga compounds are obtained by mild thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…However, the GaÐO bonds in the chloride-substituted derivatives, [R(Cl)Ga("-OH)] 2 , are generally shorter, which leads to shorter intra-annular GaÐGa vectors (2.887±2.939 A Ê ). The GaÐC bonds are some 0.03 A Ê shorter than the average found for adducts of i Pr 3 Ga (Coward et al, 2000), where the bond length sequence GaÐMe < GaÐEt < GaÐ i Pr was demonstrated. However, they are comparable to those in other " 2 -OH gallium species, such as [Me 2 Ga(" 2 -OH)] 4 (Smith & Hoard, 1959) and [ t Bu 2 Ga(" 2 -OH)] 3 (Atwood et al, 1993), although there are insuf®cient accurately determined data to con®rm a similar sequence.…”
Section: Commentmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the GaÐO bonds in the chloride-substituted derivatives, [R(Cl)Ga("-OH)] 2 , are generally shorter, which leads to shorter intra-annular GaÐGa vectors (2.887±2.939 A Ê ). The GaÐC bonds are some 0.03 A Ê shorter than the average found for adducts of i Pr 3 Ga (Coward et al, 2000), where the bond length sequence GaÐMe < GaÐEt < GaÐ i Pr was demonstrated. However, they are comparable to those in other " 2 -OH gallium species, such as [Me 2 Ga(" 2 -OH)] 4 (Smith & Hoard, 1959) and [ t Bu 2 Ga(" 2 -OH)] 3 (Atwood et al, 1993), although there are insuf®cient accurately determined data to con®rm a similar sequence.…”
Section: Commentmentioning
confidence: 70%
“…The 4:1 adduct of triisopropylgallium and 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane (Coward et al, 2000) was dissolved in dry toluene and left to crystallize at 243 K. After one week, there was evident decomposition, presumably due to hydrolysis. A few well shaped crystals present in the mixture were isolated and dried in a stream of dinitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…2b. Full crystallographic data are reported elsewhere, 11 together with 1 H and 13 C data for all the adducts listed in Table I. .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that the macrocyclic amines N 4aza crown and N 6 -aza crown form reversible adducts with triethylgallium, 14 triisopropylgallium, 14 and trimethylindium, 15 and we have now extended this approach to R 2 Zn compounds. The ready removal of alkoxide impurities from the Me 2 Zn.NEt 3 adduct has encouraged us to identify R 2 Zn-amine adducts which can be dissociated to liberate base-free R 2 Zn.…”
Section: R 2 Zn-aza Crown Adductsmentioning
confidence: 99%